Histamine Excites Rat Superior Vestibular Nuclear Neurons via Postsynaptic H1 and H2 Receptors in vitro - Qian-Xing Zhuang (Neurosignals, 2012)
The superior vestibular nucleus (SVN), which holds a key position in vestibulo-ocular reflexes and nystagmus, receives direct hypothalamic histaminergic innervations. By using rat brainstem slice preparations and extracellular unitary recordings, we investigated the effect of histamine on SVN neurons and the underlying receptor mechanisms. Bath application of histamine evoked an excitatory response of the SVN neurons, which was not blocked by the low-Ca2+/high-Mg2+ medium, indicating a direct postsynaptic effect of the amine. Selective histamine H1 receptor agonist 2-pyridylethylamine and H2 receptor agonist dimaprit, rather than VUF8430, a selective H4 receptor agonist, mimicked the excitation of histamine on SVN neurons. In addition, selective H1 receptor antagonist mepyramine and H2 receptor antagonist ranitidine, but not JNJ7777120, a selective H4 receptor antagonist, partially blocked the excitatory response of SVN neurons to histamine. Moreover, mepyramine together with ranitidine nearly totally blocked the histamine-induced excitation. Immunostainings further showed that histamine H1 and H2 instead of H4 receptors existed in the SVN. These results demonstrate that histamine excites the SVN neurons via postsynaptic histamine H1 and H2 receptors, and suggest that the central histaminergic innervation from the hypothalamus may actively bias the SVN neuronal activity and subsequently modulate the SVN-mediated vestibular functions and gaze control.